Características limnológicas da água, sedimento e efluentes em viveiros de crescimento final do camarão-da-amazônia, Macrobrachium amazonicum, submetidos a diferentes níveis de arraçoamento e tipos de despescas - Keppeler, Erlei Cassiano [UNESP] (2005)
Grow-out ponds are ecosystems at the first stages of ecological succession. In this research, a limnological study on grow-out ponds of Macrobrachium amazonicum subjected to different feed levels and harvest management was performed. Twelve 0.01 ha earthen ponds were stocked with 20 juveniles.m-2. Prawns fed commercial diet at a rate of 7 to 9% of biomass until 14a. week. Then, each three ponds were fed with 3%, 5% and 7% of prawn biomass. Three other ponds were subjected to selective harvest. After 145 days of stocking, all ponds were drained and harvested. The following water parameters were weekly determined: temperature, dissolved oxygen, oxygen biochemical demand, pH, total alkalinity, electrical conductivity, nitrate-N, nitrite-N, ammonia-N, total nitrogen, soluble orthophosphate, total phosphate, chlorophyll a, chlorophyll b, chlorophyll c, pheophytin, suspended total solids and turbidity. Limnological parameters did not show any temporal pattern. Exchange water and daily feeding slightly affected water quality and effluents. Carbon and nitrogen did not accumulated in water column or soil while phosphate was immobilized or trapped by the mud. Feeding rate and kind of harvest showed low effect on water quality, effluents and none on accumulation of carbon, nitrogen and phosphorus, in the mud. Correlation among water quality parameters are weak or absent. Data suggest that intrinsic characteristics of each pond play a major role on pond ecology